Factors related to successful aging among community-dwelling elderly in Wenzhou, China - Gu Chen-Yu; Jullamate Pornchai; Nadarajan Sivasankari; Krungkraipetch Nisakorn; Toonsiri Chanandchidadussadee (Sciendo, 2023)
Objectives: To examine the level of successful aging and the relationship between successful aging and activities of daily living (ADL), life satisfaction, social support, income, and self-efficacy among community-dwelling elderly in Wenzhou, China.